Watching Brief: The evolution and impact of COVID-19 variants B.1.1.7, B.1.351, P.1 and B.1.617 - Hermione Williams; Danielle Hutchinson; Haley Stone (University of New South Wales, 2021)
The COVID-19 pandemic continues to be perpetuated by the global emergence of variants of concern which pose issues for disease control and management by increased transmissibility, severity and vaccine resistance. This Watching Brief probes into the origins and development of these variants of concern and the repercussions of the variants of concern on public health and safety.